Advances in the Molecular Pathophysiology, Genetics, and Treatment of Primary Ovarian Insufficiency. (June 2018) - Huhtaniemi, Ilpo; Hovatta, Outi; La Marca, Antonio; Livera, Gabriel; Monniaux, Danielle; Persani, Luca; Heddar, Abdelkader; Jarzabek, Katarzyna; Laisk-Podar, Triin; Salumets, Andres; Tapanainen, Juha S.; Veitia, Reiner A.; et al.
: Primary ovarian insufficiency (POI) affects ∼1% of women before 40 years of age. The recent leap in genetic knowledge obtained by next generation sequencing (NGS) together with animal models has further elucidated its molecular pathogenesis, identifying novel genes/pathways. Mutations of >60 genes emphasize high genetic heterogeneity. Genome-wide association studies have revealed a shared genetic background between POI and reproductive aging. NGS will provide a genetic diagnosis leading to genetic/therapeutic counseling: first, defects in meiosis or DNA repair genes may predispose to tumors; and second, specific gene defects may predict the risk of rapid loss of a persistent ovarian reserve, an important determinant in fertility preservation. Indeed, a recent innovative treatment of POI by in vitro activation of dormant follicles proved to be successful. Highlights: The mechanisms underlying the formation of the ovarian reserve are generally well conserved, from Drosophila to mammals. Owing to this high degree of conservation, factors shown to regulate the ovarian reserve in mouse models are all potential candidates for identifying mutations associated with POI in humans. With the generation of genetically modified mice, much insight has been gained into the mechanisms that control the formation of the ovarian reserve and trigger the activation of primordial follicles. Comparison with animal models is complicated by the fact that the phenotype of complete gene deletion in knockout models may not be mimicked by single gene mutations. Recently innovative treatment for POI based on in vitro activation of the dormant primordial follicular pool has been developed.